The making of inclusion as structuration: empirical evidence of a multinational company. Issue 3 (11th March 2014) - Ortlieb, Renate; Sieben, Barbara
Abstract : Purpose: – The purpose of this paper is to theoretically and empirically analyse the question how organizations become inclusive – with special regard to migrants – and the potential limits to inclusion. Design/methodology/approach: – The paper develops a theoretical framework based on Giddens' structuration theory. By a firm-level case study, the paper empirically examines the theoretical propositions. Findings: – The paper proposes that inclusion bears specific kinds of the structural dimensions signification, domination and legitimation on which organizational actors draw to reproduce the inclusive organization. The empirical case reveals three areas of organizational practices – personnel recruitment and selection; training and development; meals and parties – in the making of inclusion. But the interplay of specific rules and resources also contains social practices of differentiation and hierarchization that limit inclusion. Research limitations/implications: – Future studies would benefit from considering additional socio-demographic characteristics and intersectionalities. An ethnographic approach on the basis of participant observation is also recommendable. A longitudinal empirical design focusing on causal relationships would expand the papers descriptive approach. Practical implications: – The findings suggest that organizational actors can shape the structural dimensions corresponding to an inclusive organization by acting themselves accordingly and inciting others to do so. They should be aware of processes of differentiation and hierarchization that go along with practices of inclusion. Originality/value: – Applying key arguments of structuration theory, the paper develops a comprehensive framework that considers corresponding rules and resources in detail. The empirical case study demonstrates the fruitfulness of the theoretical framework and reveals the ambivalence of organizational practices that promote inclusion.